The women's march : a novel of the 1913 woman suffrage procession - Chiaverini, Jennifer (William Morrow, an imprint of HarperCollinsPublishers, 2021)
Inspired by actual events, this novel offers a fascinating account of a crucial but little-remembered moment in American history that follows three courageous women who bravely risked their lives and liberty in the fight to win the vote.